Behavioristic Learning Theory in Islam - Imas Kania Rahman; Neng Ikrimah Aziz Zamakhsyari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Every human being needs a process to develop and continue their life. Learning is a primary need and plays an important role in supporting human future. In Western learning theory, there are three popular theories, namely: behavioristic learning theory, cognitive learning theory, and humanist learning theory. The focus in this writing is the analysis of behavioristic learning theory from an Islamic perspective. In Islam, the theory that emphasizes attitudes and behavior is the moral learning theory. This theory is commensurate with behavioristic learning theory. Coupled with the moral learning theory, it can be concluded that not all behaviorist theories are contrary to Islam. On the other hand, there are still learning theories that do not conflict with Islam, so a synthesis is needed. From the synthesis of these two learning theories, an integrated learning theory emerges that is in line with Islamic ideals, namely a collection of several principles related to learning that originate from the Al-Quran and Sunnah as well as the treasures of Muslim intellectual thought, and adopts Western learning theories that are relevant to Islam. It is hoped that this integrated learning theory can be implemented in the learning process so that it provides effective and efficient results from the learning process.